The Moderating Role of Managerial Ability and Institutional Ownership in Sustainability Report on Firm Value - Liangdri, Jeniva Zefanya; Ng, Suwandi; Tangke, Paulus (Magister Akuntansi - Universitas Atma Jaya Makassar, 2025)
The purpose of this study is to investigate the moderating role of managerial ability and institutional ownership in sustainability report on firm value. The theories used in this study are stakeholder theory and agency theory. This study uses secondary data. The data sources in this study are financial report and sustainability report published by manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2020-2022. Sample selection was carried out using the purposive sampling method so that a sample size of 22 companies was obtained over 3 years. The data analysis technique used is moderated regression analysis. The results of this study indicate that sustainability report have a positive and significant effect on firm value, managerial ability moderates the effect of sustainability report on firm value, and institutional ownership cannot moderate the effect of sustainability report on firm value.